Uncovering the Dynamics of Leadership, Learning, Innovation and Culture in Saudi Embassies - M. Baggashi, Rawan Hussain; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – The purpose of this research is to uncover the Dynamics of Leadership, Learning, Innovation and Culture in Saudi Embassies, and to analyze their impact on each other. Design/Methodology/Approach – This research employs primary and secondary research methods to understand the relationship between Leadership, Learning, Innovation and Culture at Saudi Embassies. Using quantitative data collection and analysis from 136 respondents from a cross-section of embassy employees. Findings – This research’s intention is to demonstrate the relationship and influence of Leadership Styles on Organizational Culture, Innovative Culture and Organizational Performance, respectively. The findings demonstrated the strong effect that the diverse Leadership Styles have on the described above while at the same time, exhibiting how Innovative Culture and Organizational Culture were also interchangeably significant with one another. Leadership Style had the lowest impact on Innovative Culture and Organizational Learning and requires further research to support the findings. Research Limitations/Implications – The limitations of the research displayed several element limits as it relates to the extent of leadership styles impacting organizational culture, innovative culture and organizational performance without considering external personality factors and different countries’ culture in which the embassies are located. Narrowly examining the factors and variables presented in this study, it overlooks the potential influence of many other variables not included that could affect the relationship and interconnectedness between them. Originality/Value – This research highlights the significance of relationships between Leadership, Learning, Innovation and Culture at Saudi Embassies. Keywords – Leadership Styles, Organizational Learning, Innovative Culture, Organizational Culture and Organizational Performance. JEL classification code: Z10, Z13, Z18